An economic feasibility analysis of pulsed electromagnetic field therapy as an equine therapeutic modality - Wilson, Lindsey (My University, 2019)
The purpose of this thesis is to discern the economic feasibility of Pulsed Electromagnetic Field (PEMF) Therapy as an equine therapy. This is in consideration to similar equine therapeutic modalities, such as shockwave therapy, laser therapy, and salt water hydrotherapy. The objectives of this study are to evaluate the technical advantages of PEMF over others for treating the same issues in horses and conduct scenario analysis on PEMF to determine its robustness under alternative business conditions. Primary data was used for the study, drawing on prices, time and cost estimates from professionals in the field. The constructed business model was then projected over a 10-year time frame. Revenue and expenses are based on a small mobile business model, starting off as an owner-operated business and adding an employee in Year 5 to minimize risk and increase probability of success. Vehicle and equipment purchases are financed over five years. The initial revenue model accounts for an average of 7.5 whole body treatments per day (at $60 per treatment) while working 250 days a year. Growth rate was calculated at 4 percent per year. Scenario analysis was conducted altering number of days treated, number of whole-body treatments per day, and growth rate. The results show that PEMF therapy is the most technically and operationally feasible option of the aforementioned modalities for a mobile business model due to its variety of applications, ability for use before and after performances, reasonable startup cost and lack of veterinary oversight required. The business was determined to be economically feasible under all the alternative scenarios because the estimated Net Present Value (NPV) was positive under the scenarios at 7.5% discount rate. Number of whole-body treatments were determined to be more critical on the financial performance of the business than the number of days within the confines of the scenario analyses conducted. The economic feasibility of the business was not affected by the growth rate because reducing it to zero still produced a positive NPV, even though it was a much lower NPV. The next step is to use the foregoing results to develop the business plan for building a mobile equine PEMF Therapy service in a “horse-culture” region of the country. The results will guide the development of the key performance indicators and how they may be managed to ensure financial and economic success of the business. They will also allow for the development of the critical value innovations necessary for distinguishing the business from its competitors in ways that facilitate the selection of the most profitable customers.
Keywords: Animal Health; Economic Feasibilty; Equine; Pulsed Electromagentic Field Therapy